2023
DOI: 10.1021/acsnano.3c04748
|View full text |Cite
|
Sign up to set email alerts
|

Combining Solid Solution Strengthening and Second Phase Strengthening for Thinning Li Metal Foils

Abstract: Thin lithium (Li) metal foils have been proved to be indispensable yet elusive for practical high-energy-density lithium batteries. Currently, the realization of such thin foils (<50 μm) is impeded by the inferior mechanical processability of metallic Li. In this work, we demonstrate that the combination of solid solution strengthening and second phase strengthening, achieved by the addition of silver fluoride (AgF) to Li metal, can substantially enhance both the strength and ductility of metallic Li. Benefiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 41 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…However, fabricating and stabilizing Li thin foils <50 µm are still daunting due to the poor processability of Li and its inherent instability in LEs. [ 25 ] Although P–Li can also be rolled to a thickness of ≈77 µm (Figure 6c), Li foil is tightly sticking onto the roller, and obvious cracks appear, indicating a mechanical failure. Here, it is found that a doping of 5 wt% AlN substantially improves the machinability of Li, allowing a self‐supporting foil of only 35 µm (Figure 6d).…”
Section: Resultsmentioning
confidence: 99%
“…However, fabricating and stabilizing Li thin foils <50 µm are still daunting due to the poor processability of Li and its inherent instability in LEs. [ 25 ] Although P–Li can also be rolled to a thickness of ≈77 µm (Figure 6c), Li foil is tightly sticking onto the roller, and obvious cracks appear, indicating a mechanical failure. Here, it is found that a doping of 5 wt% AlN substantially improves the machinability of Li, allowing a self‐supporting foil of only 35 µm (Figure 6d).…”
Section: Resultsmentioning
confidence: 99%
“…By incorporating silver into lithium metal to form LiAg alloys, the machinability of lithium metal can be greatly improved, enabling the fabrication of ultrathin lithium foils. 34,35 By utilizing the lithiophilicity of LiZn alloys, the molten LiZn alloys can be easily spread on a copper foil and form a controllable thickness negative electrode. 18 Additionally, LiSn alloys enable the large-scale printing of flexible ultrathin (15 μm) lithium alloy negative electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The lithiation induced alloying process involves the continuous formation of Li‐containing intermediates with gradually enhanced Li solubility, leading to higher gravimetric capacities as compared to graphite anodes that are based on intercalation chemistry. [ 1–9 ] Li‐M alloys (M = Zn, Al, Ag, Sn, etc.) have also been investigated as preferential nucleation sites in metallic batteries, mitigating the nucleation overpotentials.…”
Section: Introductionmentioning
confidence: 99%